2008
DOI: 10.1021/jp8033006
|View full text |Cite
|
Sign up to set email alerts
|

Stable Geometric and Electronic Structures of Gold-Coated Nanoparticles M@Au12 (M = 5d Transition Metals, from Hf to Hg): Ih or Oh?

Abstract: The geometric and electronic structures of 5d transition metal “impurities” Hf to Hg encapsulated in icosahedral and cuboctahedral Au12 cages have been investigated theoretically. The best density functional results of the small molecules Au2, AuH, AuCl, and AuCu were obtained for the geometric structures with Xα, and for the electronic energies of those frozen structures with VBP. The same procedure was then applied to the clusters. At the zeroth order regular relativistic approximation ZORA, both at the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…It is interesting to note that the gold cluster Au 12 is known to have a cage‐like shape and thus we suppose that the structure of Au 12 P n + ( n = 1, 2, 4) might be an endohedral type, i.e. gold‐covered phosphorus P n @Au 12 ( n = 1, 2, 4) clusters; but the structure of P n ‐Au 12 cluster‐cluster associates cannot be excluded.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is interesting to note that the gold cluster Au 12 is known to have a cage‐like shape and thus we suppose that the structure of Au 12 P n + ( n = 1, 2, 4) might be an endohedral type, i.e. gold‐covered phosphorus P n @Au 12 ( n = 1, 2, 4) clusters; but the structure of P n ‐Au 12 cluster‐cluster associates cannot be excluded.…”
Section: Resultsmentioning
confidence: 95%
“…An interesting structure of gold phosphide is that proposed by Sevillano et al [42] Several polyphosphide compounds have also been synthesised [43] and a theoretical study of bonding in the ternary gold polyphosphides, Au 2 MP 2 with M = Pb, Tl, or Hg, has shown that the crystal structure contains structural motifs of heterocyclic Au 2 P 6 and Au 4 P 6 'units' forming parallel channels which are filled by Pb, Tl or Hg atoms. 14 It is interesting to note that the gold cluster Au 12 is known to have a cage-like shape [44][45][46] and thus we suppose that the structure of Au 12 P n + (n = 1, 2, 4) might be an endohedral type, i.e. gold-covered phosphorus P n @Au 12 (n = 1, 2, 4) clusters; but the structure of P n -Au 12 cluster-cluster associates cannot be excluded.…”
Section: The Structure Of the Clustersmentioning
confidence: 99%
“…Zhai et al [23] investigated M@Au 12 − (M = V, Nb, Ta), and Qiu et al [25] reported M@Au 12 (M = W, Pt, Au, Hg). Long et al studied the geometric and electronic structures of endohedral M@Au 12 (M = 5 d transition metals, from Hf to Hg) [26]. Very recently, Wang et al [27] investigated structural and photoelectron spectroscopic properties of the anionic Cu@Au 16 − and Cu@Au 17 − clusters both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…A novel Au20 tetrahedral structure identified by photoelectron spectroscopy correlates with relativistic density functional theory (DFT) calculations. 2 Fa and Dong 3 identified a stable tube-like Aun (n= [26][27][28] cluster with scalar, relativistic, all-electron DFT. Highly stable"golden fullerene"Au32 and Au42 clusters have been reported, 4,5 and core-shell structures have been verified by recent studies on Au34 and Au58 clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Since Pykko 16 and Li 17 et al first reported the existence of highly stable Au12W via photoelectron spectroscopy, a considerable amount of experimental and theoretical work has been carried out on Au clusters doped with other impurity atoms. 11,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Most of these studies have focused on Au12 doped with transition-metal (TM) atoms. The high Ih or Oh symmetry of the lowest-energy Au12TM clusters is attributed to the strong relativistic effect, aurophilic attraction, and 18-electron bonding to the 4s, 5s, and 6s shells of the central heteroatom.…”
Section: Introductionmentioning
confidence: 99%